2015
DOI: 10.3109/09537104.2014.1003291
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic acid-stimulated platelet tests: Identification of patients less sensitive to aspirin treatment

Abstract: Serum thromboxane-B2 (TxB2), together with arachidonic acid (AA)-induced platelet aggregation, are, at the moment, the most used tests to identify patients displaying high on-aspirin treatment platelet reactivity (HAPR). Both tests are specific for aspirin action on cyclooxygenase-1. While the correlation between serum TxB2 assay and clinical outcome is established, data are conflicting with regard to aspirin treatment and a possible association with AA-stimulated platelet markers and clinical outcome. To unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Platelet aggregation was evaluated in PRP in a four-channel aggregometer (AggRam, Helena Laboratories, Beaumont, Texas, United States) according toTemperilli et al 29 The results are reported as the percentage of aggregation observed after 4 minutes of stimulation (%PA) in response to ADP (2 μM) and primary maximal platelet aggregation in response to ADP (0.8 μM) (Helena Laboratories, Beaumont, Texas, United States). Results were considered statistically significant if a pvalue of less than 0.05 was reached.…”
Section: Platelet Aggregationmentioning
confidence: 99%
“…Platelet aggregation was evaluated in PRP in a four-channel aggregometer (AggRam, Helena Laboratories, Beaumont, Texas, United States) according toTemperilli et al 29 The results are reported as the percentage of aggregation observed after 4 minutes of stimulation (%PA) in response to ADP (2 μM) and primary maximal platelet aggregation in response to ADP (0.8 μM) (Helena Laboratories, Beaumont, Texas, United States). Results were considered statistically significant if a pvalue of less than 0.05 was reached.…”
Section: Platelet Aggregationmentioning
confidence: 99%
“…In patients under chronic treatment, the compliance was assessed both by interview and as arachidonic acid-induced platelet aggregation (0.75 mmol/L) < 10%. 17 In our study, were excluded all those patients with cardiovascular diseases including: Ischemic Heart Disease (IHD), cerebrovascular disease or transient ischemic attack, established peripheral vascular disease, and class III to IV heart failure, in the previous 15 days.…”
Section: Patientsmentioning
confidence: 99%
“…Platelet aggregation (PA) was performed as previously described [18]. PA was evaluated both in PRP and PFP using AggrRam aggregometer (Helena Laboratries, Beaumont, Texas, USA).…”
Section: Platelet Aggregationmentioning
confidence: 99%